Virtual-Based Academic Supervision of School Based on Improving The Quality of Islamic Religious Education in Elementary School - Slamet Riadi (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2022)
Academic Supervision aims to collect information or real conditions of the implementation of the duties of educators and education staff in accordance with their main tasks as a basis for conducting coaching, accreditation, and follow-up to improve the quality of student learning. The further goal is to use the results of accreditation to improve quality. The top target of Supervision is the development of a continuous quality improvement process; increasing the habit of carrying out tasks from the start with measurable quality, and getting used to each stage of work with clear quality. In the end, Supervision fosters a quality culture because quality is a culture that always upholds high targets at every step of the activity. Activities in this research analysis, through data reduction steps, data presentation, as well as drawing conclusions and verification. Principal's Academic Supervision Planning by compiling a supervision program plan which is carried out every year before the new school year begins. This is an illustration so that when entering the new school year all programs are ready to be implemented. The implementation of the Principal's Academic Supervision is by providing assistance in preparing RPP administration for Islamic Religious Education teachers through online, carrying out assessments of student learning outcomes. As well as the supervision model used in the academic Supervision carried out by the principal, namely the clinical model and the virtual-based artistic model. The implications of the Principal's Academic Supervision in improving the quality of Islamic Religious Education are learning effectiveness, increasing student achievement and achieving curriculum targets